The impact of patient-centered care on health outcomes in adolescents living with diabetes - Rashida Farhad Vasanwala; Amos Lim; Lim Soo Ting; Lim Pei Kwee; Hui Yuen Ching; Tan Xiang Feng (The Beryl Institute, 2022)
There is increasing evidence from research studies that suggest patient-centered care has a relationship with good clinical outcomes. In Singapore, there are no studies done to assess and address the issue of patient-centered care and its association with the adolescent's ability to manage their chronic medical condition, such as Type 1 Diabetes Mellitus. The relationship between the patient and clinicians has changed from a paternalistic form to a position which aims to foster patient-centered care. More importantly, this study aims to show the adolescent's readiness and ability to assume a more mature role in management of their own medical condition. Data collection involved 85 adolescents with diabetes who were surveyed during their follow-up outpatient clinic visit at KK Women's and Children's Hospital (KKH) Diabetes Transition Clinic. The study offers important clinical and nursing implications as well as policy contributions. Improved patient-provider communication as well as high quality discharge, care transition and emotional support from providers fostered by patient-centered care are likely to contribute to better patient reported psychosocial health outcomes. These findings imply that public healthcare leaders have to place emphasis in the patient and their families' experience equivalent to those in patient safety, clinical quality, and hospital finance. Experience Framework This article is associated with the Quality & Clinical Excellence lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Quality%20%26%20Clinical%20Excellence%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.